A Two-State Cell Damage Model Under Hyperthermic Conditions: Theory and In Vitro Experiments - Feng, Yusheng (2008)
The ultimate goal of cancer treatment utilizing thermotherapy is to eradicate tumors and minimize damage to surrounding host tissues. To achieve this goal, it is important to develop an accurate cell damage model to characterize the population of cell death under various thermal conditions. The traditional Arrhenius model is often used to characterize the damaged cell population under the assumption that the rate of cell damage is proportional to exp(−E(a)/RT), where E(a) is the activation energy, R is the universal gas constant, and T is the absolute temperature. However, this model is unable to capture transition phenomena over the entire hyperthermia and ablation temperature range, particularly during the initial stage of heating. Inspired by classical statistical thermodynamic principles, we propose a general two-state model to characterize the entire cell population with two distinct and measurable subpopulations of cells, in which each cell is in one of the two microstates, viable (live) and damaged (dead), respectively. The resulting cell viability can be expressed as C(τ, T) = exp(−Φ(τ, T)/kT)/(1+exp(−Φ(τ, T)/kT)), where k is a constant. The in vitro cell viability experiments revealed that the function Φ(τ, T) can be defined as a function that is linear in exposure time τ when the temperature T is fixed, and linear as well in terms of the reciprocal of temperature T when the variable τ is held as constant. To determine parameters in the function Φ(τ, T), we use in vitro cell viability data from the experiments conducted with human prostate cancerous (PC3) and normal (RWPE-1) cells exposed to thermotherapeutic protocols to correlate with the proposed cell damage model. Very good agreement between experimental data and the derived damage model is obtained. In addition, the new two-state model has the advantage that is less sensitive and more robust due to its well behaved model parameters.